Critical Gaps in the World’s Largest Electronic Medical Record: Ad Hoc Nursing Narratives and Invisible Adverse Drug Events - Hurdle, John F. (American Medical Informatics Association, 2003)
The Veterans Health Administration (VHA), of the U.S. Department of Veteran Affairs, operates one of the largest healthcare networks in the world. Its electronic medical record (EMR) is fully integrated into clinical practice, having evolved over several decades of design, testing, trial, and error. It is unarguably the world’s largest EMR, and as such it makes an important case study for a host of timely informatics issues. The VHA consistently has been at the vanguard of patient safety, especially in its provider-oriented EMR. We describe here a study of a large set of adverse drug events (ADEs) that eluded a rigorous ADE survey based on prospective EMR chart review. These numerous ADEs were undetected (and hence invisible) in the EMR, missed by an otherwise sophisticated ADE detection scheme. We speculate how these invisible nursing ADE narratives persist and what they portend for safety re-engineering.